Multitasking with laptops during Meetings. - BENBUNAN-FICH, RAQUEL; TRUMAN, GREGORY E. (Communications of the ACM, 2009)
The article discusses the use of laptops for multitasking during professional meetings, examining the prevailing manner in which individuals use computers to engage in more than one task concurrently in the context of face-to-face (F2F) meetings. Computers may be used for compliant uses, such as taking notes, or distracting uses, such as playing computer games, the authors note. Other topics include computer-based multitasking levels that vary across meeting activities as a factor of attention requirements.